2009
DOI: 10.1007/s11099-009-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between foliar carbon isotope discrimination with potassium concentration and ash content of the riparian plants in the extreme arid region of China

Abstract: Carbon isotope discrimination (Δ) has been proposed as an indirect estimation criterion for water use efficiency in C 3 plants. Because of the higher cost for Δ analysis, ash content or K concentration has been proposed as an alternative criterion for Δ in many species. In five typical habitats of the extreme arid Ejina desert oasis in northwest of China, the seasonal variations of foliar Δ, ash content, and potassium (K) concentration were researched in two constructive desert riparian plants (Populus euphrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
(101 reference statements)
1
12
0
Order By: Relevance
“…Relationships between d 13 C and C Previous studies have reported negative correlations between d 13 C and ash or mineral content (Cao et al 2009;Merah et al 2001;Zhao et al 2007;Zhu et al 2010). Generally, C was negatively correlated with ash or mineral content (Zhou et al 2013).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Relationships between d 13 C and C Previous studies have reported negative correlations between d 13 C and ash or mineral content (Cao et al 2009;Merah et al 2001;Zhao et al 2007;Zhu et al 2010). Generally, C was negatively correlated with ash or mineral content (Zhou et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…However, while Cao et al (2009) and Zhao et al (2007) found negative relationships between d 13 C and K for Tamarix ramosissima, Artemisia ordosica, and Hedysarum scoparium, as well, they also found positive relationships for Populus euphratica and Caragana korshinskii.…”
Section: Ofmentioning
confidence: 88%
See 2 more Smart Citations
“…Mg, which occupies the center of the porphyrin nucleus of the chlorophyll molecule, has an important function in activating enzymes related to the synthesis of protein, RNA and DNA [21]. In addition, a negative correlation between ash content and δ 13 C has been widely observed [22][27]. This is because minerals are mostly passively transported in plant organs via the xylem flux and accumulated in place, so a plant that needs more water for the same biomass accumulation (lower δ 13 C) would be proportionally richer in minerals (higher ash content).…”
Section: Introductionmentioning
confidence: 99%